A Novel Bifidobacterium longum Subsp. longum T1 Strain from Cow's Milk: Homeostatic and Antibacterial Activity against ESBL-Producing Escherichia coli - Andrey V. Machulin; Vyacheslav M. Abramov; Igor V. Kosarev; Evgenia I. Deryusheva; Tatiana V. Priputnevich; Alexander N. Panin; Ashot M. Manoyan; Irina O. Chikileva; Tatiana N. Abashina; Dmitriy A. Blumenkrants; Olga E. Ivanova; Tigran T. Papazyan; et al. (MDPI AG, 2024)
Background/Objectives: The global emergence of antibiotic-resistant zooanthroponotic Escherichia coli strains, producing extended-spectrum beta-lactamases (ESBL-E) and persisting in the intestines of farm animals, has now led to the development of a pandemic of extra-intestinal infectious diseases in humans. The search for innovative probiotic microorganisms that eliminate ESBL-E from the intestines of humans and animals is relevant. Previously, we received three isolates of bifidobacteria: from milk of a calved cow (BLLT1), feces of a newborn calf (BLLT2) and feces of a three-year-old child who received fresh milk from this calved cow (BLLT3). Our goal was to evaluate the genetic identity of BLLT1, BLLT2, BLLT3 isolates using genomic DNA fingerprinting (GDF), to study the tolerance, adhesion, homeostatic and antibacterial activity of BLLT1 against ESBL-E. Methods: We used a complex of microbiological, molecular biological, and immunological methods, including next generation sequencing (NGS). Results: GDF showed that DNA fragments of BLLT2 and BLLT3 isolates were identical in number and size to DNA fragments of BLLT1. These data show for the first time the possibility of natural horizontal transmission of BLLT1 through with the milk of a calved cow into the intestines of a calf and the intestines of a child. BLLT1 was resistant to gastric and intestinal stresses and exhibited high adhesive activity to calf, pig, chicken, and human enterocytes. This indicates the unique ability of BLLT1 to inhabit the intestines of animals and humans. We are the first to show that BLLT1 has antibacterial activity against ESBL-E strains that persist in humans and animals. BLLT1 produced 145 ± 8 mM of acetic acid, which reduced the pH of the nutrient medium from 6.8 to 5.2. This had an antibacterial effect on ESBL-E. The genome of BLLT1 contains ABC-type carbohydrate transporter gene clusters responsible for the synthesis of acetic acid with its antibacterial activity against ESBL-E. BLLT1 inhibited TLR4 mRNA expression induced by ESBL-E in HT-29 enterocytes, and protected the enterocyte monolayers used in this study as a bio-model of the intestinal barrier. BLLT1 increased intestinal alkaline phosphatase (IAP) as one of the main molecular factors providing intestinal homeostasis. Conclusions: BLLT1 shows promise for the creation of innovative functional nutritional products for humans and feed additives for farm animals that will reduce the spread of ESBL-E strains in the food chain.